Examination of Factors Affecting Life Satisfaction of University Students: Muğla Case - Uçurmaz, Burçin; Karapınar, Meryem; Demirel, Aykut Can (Fırat University, 2025)
The main purpose of this research is to examine the Life Satisfaction levels of university students according to some variables. Within the framework of this purpose, the effects of students' socio-demographic characteristics, participation in artistic and sportive activities, relationships established in their social lives and perceived academic achievement on their Life Satisfaction levels were examined. In the research, correlational research model, one of the quantitative research designs, was adopted and the sample group was formed using simple random sampling method. 362 students participated in the research. The analyses revealed that family attitudes, income and academic achievement perceptions, chronic illness/disability, participation sports and cultural activities, and having a close/special friend affected students' Life Satisfaction levels. Therefore, from the analysis, it was found that the Life Satisfaction levels of the students who defined their family attitudes as democratic were higher than those of the students who defined their family attitudes as indifferent. The results of the research showed that positive changes in students' academic achievement and income perceptions can positively affect their Life Satisfaction levels. Moreover, it was found that the participants' Life Satisfaction levels did not differ in terms of gender, age, number of siblings, housing type and romantic relationship variables.

Bu araştırmanın temel amacı üniversite öğrencilerinin Yaşam Doyumu düzeylerinin bazı değişkenlere göre incelenmesidir. Bu amaç çerçevesinde öğrencilerin sosyo-demografik özellikleri, sanatsal ve sportif faaliyetlere katılımları, sosyal yaşamlarında kurduğu ilişkiler ve algılanan akademik başarılarının Yaşam Doyumu düzeylerine etkileri incelenmiştir. Araştırmada nicel araştırma desenlerinden korelasyonel araştırma modeli benimsenmiş ve örneklem grubu basit rastgele örnekleme yöntemi kullanılarak oluşturulmuştur. Araştırmaya 362 öğrenci katılmıştır. Yapılan analizlerde öğrencilerin aile tutumlarının, gelir ve akademik başarı algılarının, kronik hastalık/engellilik durumlarının, spor ve kültürel faaliyetlere katılımlarının ve yakın/özel bir arkadaşa sahip olmalarının Yaşam Doyumu düzeylerini etkilediği sonucuna ulaşılmıştır. Elde edilen analizler sonucunda aile tutumlarını demokratik olarak tanımlayan öğrencilerin Yaşam Doyumu düzeyleri ilgisiz aile tutumlarına sahip olanlara göre daha yüksek olduğu anlaşılmıştır. Araştırma sonuçları öğrencilerin akademik başarı ve gelir algılarının pozitif yönde değişiminin Yaşam Doyumu düzeylerini de pozitif yönde etkileyebileceğini göstermiştir. Diğer taraftan katılımcıların cinsiyet, yaş, kardeş sayısı, barınma tipi ve romantik ilişki değişkenleri açısından Yaşam Doyumu düzeylerinin farklılaşmadığı anlaşılmıştır.
Üniversite Öğrencilerinin Yaşam Doyumlarını Etkileyen Faktörlerin İncelenmesi: Muğla Örneği
Keywords: Counselling; Wellbeing and Community Services; Danışmanlık; Refah ve Toplum Hizmetleri; Social Work (Other); Sosyal Hizmetler (Diğer); Child and Adolescent Development; Çocuk ve Ergen Gelişimi